Antiplasmodial, Antimicrobial and Cytotoxic Activities of Extracts from Selected Medicinal Plants Growing in Tanzania. Issue 2 (3rd March 2020) - Begum, Sartaz; Munissi, Joan J.E.; Buriyo, Amelia S.; Makangara, John J.; Lucantoni, Leonardo; Avery, Vicky M.; Erdelyi, Mate; Nyandoro, Stephen S.
Abstract: This paper reports on the evaluation of antiplasmodial, antimicrobial and cytotoxic activities of extracts from eleven plant species traditionally used by some Tanzanian coastal communities for treatment of malaria, microbial infections and related ailments. Crude extracts from selected plant species namely Acacia zanzibarica, Danais xanthorrhoea, Diospyros loureiriana ssp . rufescens, Erythrina sacleuxii, Newtonia paucijuga, Pentas lanceolata, Scorodophloeus fischeri, Stuhlmannia moavi, Tarenna pavettoides, Tessmannia burttii and Toussaintia orientalis growing in Tanzania were investigated using an imaging-based assay (antiplasmodial), well diffusion and microplate dilution methods (antimicrobial) and human embryonic kidney cells (HEK 293) and brine shrimp larvae assays (toxicity). The extracts exhibited activities of varying potencies and cytotoxicity with IC50 values ranging from 0.45 ± 0.09 to 75.70 ± 24.19 μg/mL against Plasmodium falciparum (3D7 strain), MIC ranging from 0.25 to 2.0 mg/mL (against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Candida albicans and Cryptococcus neoformans ), LC50 ranging from 0.75 to 1000 μg/mL against brine shrimp larvae ( Artemia salina ) and IC50 ranging from 4.02 ± 1.05 to more than 289 μg/mL against HEK 293 cells. The observed bioactivities of some of the investigated plant extracts validate their ethnomedicinal use and are indicative of the presence of bioactive ingredients for further phytochemical investigations.